Pengaruh Pembelajaran Bahasa Indonesia Menggunakan Model Project Based Learning (PJBL) Berbantuan Media Interaktif Berbasis Canva Ditinjau Dari Kemampuan Awal Terhadap Menulis Teks Prosedur Siswa Sekolah Dasar - Benni Geofani; Abdul Muktadir; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2026)
This study aimed to examine the effect of Indonesian language learning using the Project Based Learning (PjBL) model assisted by Canva-based interactive media on students’ procedural text writing skills and to compare students with high and low initial abilities. The subjects were 40 fifth-grade students of SD Negeri 4 Pasemah Air Keruh, divided into experimental and control groups (20 students each). Using a quasi-experimental design (Matching Only Pretest-Posttest Control Group Design), data were collected through tests, observations, interviews, and documentation. Results showed that the experimental class’s average score increased from 10.45 to 16.25, while the control class improved from 10.45 to 11.95. ANOVA results indicated a significant difference (p = 0.000 < 0.05), proving that the PjBL model with Canva-based media effectively enhanced students’ procedural text writing skills compared to conventional methods.